Converting a Story from Students’ Own Language in English to Increase Speaking Ability - Ismail Ismail (Majesty Journal, 2019)
This study aimed to examine whether converting students’ own local stories into English could improve their speaking ability and to identify students’ responses toward the use of short stories in speaking class. The study employed a quasi-experimental design involving 30 fourth-semester students of the English Education Department at STKIP Muhammadiyah Enrekang, who were randomly assigned into an experimental group and a control group, with 15 students in each group. Data were collected through speaking tests and a questionnaire. The speaking test was administered before and after the treatment, while the questionnaire was used to explore students’ responses to the instructional strategy. The findings revealed that the experimental group showed a significant improvement in speaking performance after receiving the treatment through short story conversion and retelling activities, whereas the control group did not show meaningful progress under conventional instruction. The students also expressed positive responses toward the use of short stories, indicating that this strategy helped them speak more confidently, enriched vocabulary use, reduced anxiety, and created a more meaningful speaking experience. The study concludes that converting stories from students’ own language into English is an effective instructional strategy for improving speaking ability in EFL classrooms, particularly because it connects language learning with familiar cultural content and encourages active oral participation.